2020
DOI: 10.1002/jhbp.768
|View full text |Cite
|
Sign up to set email alerts
|

Optimal timing of laparoscopic cholecystectomy after gallbladder drainage for acute cholecystitis: A multi‐institutional retrospective study

Abstract: BackgroundThere is no consensus on the optimal timing of laparoscopic cholecystectomy (LC) after gallbladder drainage for acute cholecystitis (AC). To obtain evidence for a consensus, we investigated surgical outcomes of LC after gallbladder drainage with respect to the time elapsed from gallbladder drainage to surgery in a multi‐institutional retrospective study.MethodsThis study enrolled 347 patients who underwent LC after gallbladder drainage for AC at 15 institutions. Surgical outcome of LC was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…In our study, 51 patients (59.3%) with ETGS and 13 patients (37.1%) with PC further underwent cholecystectomy without surgical complications, with a median time from gallbladder drainage to cholecystectomy of 130 days and 72 days, respectively. In a multi-center retrospective study of laparoscopic cholecystectomy after PC and endoscopic naso gallbladder drainage for acute cholecystitis (n = 347) reported by Tomimaru et al [ 25 ], the time for cholecystectomy in their series were within 2 weeks and after 1 month, respectively, with good surgical outcomes. In a study of cholecystectomy after EUGS (n = 13) and PC (n = 21) reported by Saumoy et al [ 26 ], all patients had technically successful with the mean time from gallbladder drainage to cholecystectomy of 156 days and 80 days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 51 patients (59.3%) with ETGS and 13 patients (37.1%) with PC further underwent cholecystectomy without surgical complications, with a median time from gallbladder drainage to cholecystectomy of 130 days and 72 days, respectively. In a multi-center retrospective study of laparoscopic cholecystectomy after PC and endoscopic naso gallbladder drainage for acute cholecystitis (n = 347) reported by Tomimaru et al [ 25 ], the time for cholecystectomy in their series were within 2 weeks and after 1 month, respectively, with good surgical outcomes. In a study of cholecystectomy after EUGS (n = 13) and PC (n = 21) reported by Saumoy et al [ 26 ], all patients had technically successful with the mean time from gallbladder drainage to cholecystectomy of 156 days and 80 days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis and treatment of GB lesions have been well discussed. [15][16][17][18][19][20][21] In particular, the differentiation between benign lesions and malignant lesions is a major issue of concern. Various approaches have been attempted for the accurate diagnosis of GB lesions including analysis of the enhancement pattern on contrast-enhanced US (CE-US) or contrast-enhanced EUS (CE-EUS).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis and treatment of GB lesions have been well discussed 15‐21 . In particular, the differentiation between benign lesions and malignant lesions is a major issue of concern.…”
Section: Discussionmentioning
confidence: 99%
“…A sound knowledge of vascular anatomy and potential variants is important to avoid vascular injury in both open surgery as well as laparoscopic surgery. Laparoscopic cholecystectomy is the standard treatment for benign gallbladder disease 6,7 and there is emerging evidence that supports laparoscopic cholecystectomy for the treatment of early gallbladder cancer. 6,8 At laparoscopy, vascular injury may occur either during creation of pneumoperitoneum or during dissection within Calot's triangle.…”
Section: Relevance Of Vascular Anatomymentioning
confidence: 99%